Arabic Textbook Preparation For Indonesian Learners: Between Theoretical Concepts and Practical Reality - Pahlefi, M. Riza; Mutmainah, Fatimah Azzahra; Karimah, Lina Husnul; Rifai, Arief Bahtiar (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study aims to analyze the theoretical principles and practical realities of Arabic textbook development for Madrasah Aliyah published by the Ministry of Religious Affairs in 2020. Using a descriptive qualitative approach through literature review and content analysis, this study focuses on four key principles in Arabic textbook development, that is sociocultural, psychological, linguistic, and pedagogical. The results show that the textbook integrates Islamic values and local Indonesian contexts (sociocultural), presents materials progressively according to students’ development stages (psychological), applies modern fusha Arabic balanced with four language skills (linguistic), and aligns objectives, materials, and evaluations with the national curriculum (pedagogical). Overall, the textbook fulfills the theoretical framework of Arabic textbook design for non-Arab learners while still requiring improvement in communicative and evaluative components. These findings contribute to the development of more adaptive and contextual Arabic language teaching materials for Indonesian learners.